SX-Ella Danis stent in massive upper gastrointestinal bleeding in cirrhosis – a case series - Jain, Mayank; Balkrishanan, Mahadevan; SNK, Chenduran; CGS, Sridhar; Ramakrishnan, Ravi; Venkataraman, Jayanthi (Clinical and Experimental Hepatology, 2018)
We report our experience of three cases of decompensated cirrhosis with massive upper gastrointestinal bleeding, which required insertion of an SX-Ella Danis stent for hemostasis. The procedure is safe and effective.